Comparison of Prostaglandin Analogue and Prostaglandin Analogue/Beta-blockers Fixed Combination in Patients with Primary Open Angle Glaucoma - Hoxha , Gentian; Spahiu, Kelmend; Kaçaniku, Gazmend; Ismaili, Mimoza; Ismajli-Hoxha , Fëllanza (New Horizons in Medicine and Medical Research Vol. 2, 2022)
Purpose: To compare the efficacy and safety of intraocular pressure (IOP)-lowering travoprost 0.004 percent and travoprost 0.004 percent and beta-blocker 0.5 percent fixed combination ophthalmic solution in patients with open-angle glaucoma and ocular hypertension. Methods: In this prospective, multicenter clinical trial, 62 patients were given either travoprost 0.004% (n = 31) or travoprost 0.004% and beta-blocker 0.50% (n = 31). Over a two-year period, efficacy and safety were compared across treatment groups. Each group's IOP reduction and adverse events were assessed at 3, 6, 12, and 24 months. Results: Mean IOP at the first visit in the travoprost 0.004% group was 26.4 (SD ± 2.1), and travo- prost 0.004%/timolol 0.5% group was 26.3 (SD ± 2.1). Mean IOP after 24 months in the travoprost 0.004% group was 20.5 (SD ± 1.5) and travoprost 0.004%/timolol 0.5% group was 18.5 (SD ± 1.5). There were statistically sig- nificant differences in IOP in both eyes after third visit (after 1 year) and fourth visit (after 2 years). Conclusion: Travoprost 0.004 percent/timolol 0.5 percent produced clinically relevant IOP reductions in patients with open-angle glaucoma or ocular hypertension that were greater than those produced by travoprost 0.004 percent alone after 2 years of treatment.